2013
DOI: 10.1053/j.ajkd.2013.02.363
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle-Related Factors, Obesity, and Incident Microalbuminuria: The CARDIA (Coronary Artery Risk Development in Young Adults) Study

Abstract: Background Modifiable lifestyle-related factors are associated with risk of coronary heart disease and may also influence kidney disease risk. Study Design Community-based prospective cohort study. Setting & Participants 2354 African-American and white participants ages 28–40 years, without baseline microalbuminuria or estimated glomerular filtration rate <60 ml/min/1.73 m2 recruited from four U.S. centers: Birmingham AL, Chicago IL, Minneapolis MN, and Oakland CA. Factors Current smoking, physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(101 citation statements)
references
References 43 publications
4
94
0
3
Order By: Relevance
“…Height and weight were measured, and body mass index (BMI) was calculated as weight in kilograms divided by height in meters squared. Adherence to the Dietary Approaches to Stop Hypertension (DASH) diet was calculated using the methods described by Chang et al 12. Eight dietary components comprise the DASH adherence score.…”
Section: Methodsmentioning
confidence: 99%
“…Height and weight were measured, and body mass index (BMI) was calculated as weight in kilograms divided by height in meters squared. Adherence to the Dietary Approaches to Stop Hypertension (DASH) diet was calculated using the methods described by Chang et al 12. Eight dietary components comprise the DASH adherence score.…”
Section: Methodsmentioning
confidence: 99%
“…Higher BMI is associated with the presence 8 and development [9][10][11] of proteinuria in individuals without kidney disease. Furthermore, in numerous large population-based studies, higher BMI appears associated with the presence 8,12 and development of low estimated glomerular filtration rate (GFR), 9,10,13 with more rapid loss of estimated GFR over time, 14 and with the incidence of ESRD.…”
Section: Association Of Obesity With Ckd and Other Renal Complicationsmentioning
confidence: 99%
“…There is mounting evidence that poor dietary patterns may lead to kidney disease (6,7). Until recently, dietary studies in CKD have focused mainly on protein intake, which have suggested a modest benefit with protein restriction (8,9).…”
Section: Introductionmentioning
confidence: 99%